2008
DOI: 10.1007/s10661-008-0452-x
|View full text |Cite
|
Sign up to set email alerts
|

Metal pollution records in core sediments of some Red Sea coastal areas, Kingdom of Saudi Arabia

Abstract: In the last three decades, the industrial and human activities in the coastal area of Saudi Arabia have increased dramatically and resulted in the continuous invasion of different types of pollutants including heavy metals. Seven sediment cores were collected from three major industrialized areas; Jeddah, Rabigh and Yanbu, along the coast of Saudi Arabia to determine the spatial and temporal distribution of metals and to assess the magnitude of pollution and their potential biological effects. Sediments were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(73 citation statements)
references
References 37 publications
4
66
3
Order By: Relevance
“…Badr et al [1] indicated that pollution with heavy metals including cadmium increased in Jeddah, Rabeg and T. Al Ibrahim et al…”
Section: Introductionmentioning
confidence: 99%
“…Badr et al [1] indicated that pollution with heavy metals including cadmium increased in Jeddah, Rabeg and T. Al Ibrahim et al…”
Section: Introductionmentioning
confidence: 99%
“…International literature identifies many factors or indices to understand toxicity or polution levels associated with these heavy metals such as bioconcentration factors (BCF), pollution index (PI), integrated pollution index (IPI), and geo-accumulation index (Igeo) (Usman et al, 2013;Agoramoorthy et al, 2008). However, the PLI is one of the good established pollution indicators that has been commonly used to evaluate the quality of coastal sediment in Saudi Arabia (Badr et al, 2009) and other parts of the world such as France, USA and Ireland since 1979 (Wilson, 2003).…”
Section: Heavy Metal Pollution In the Mangrovementioning
confidence: 99%
“…The assessment of the contamination extent by metals in sediments was further calculated using the Pollution Load Index (PLI) [40] with the heavy metal data and world shale average values of the respective metals [35,41,42]. It provides a summative indication of the overall level of heavy metal pollution in a particular sample.…”
Section: Pollution Load Indexmentioning
confidence: 99%